Pengaruh Kesejahteraan Karyawan, Lingkungan Kerja, dan Hubungan Interpersonal terhadap Produktifitas Kerja - Nurul Ariffaeni Islami; Rensi Suryanti; Riski Eko Ardianto; Ahmad Salabi; Budi Sulistiyo Nugroho (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Along with the increasingly tight business competition, many companies are required to take certain steps in facing competition in this global era. Employee welfare is one of the strict considerations that must be considered by the company, it is no wonder that in today's era many companies need skilled workers in terms of Human Resource management because of the awareness of the importance of HR management. In this study, this study uses a quantitative research type. This study aims to determine the effect of employee welfare, work environment, and interpersonal relationships on work productivity. And the population obtained in this study was 150 respondents. The analysis technique in this study used Multiple Linear Regression with SPSS software. Based on the results of the research conducted, it can be concluded that employee welfare, work environment, and interpersonal relationships affect work productivity.